PENGEMBANGAN PRODUK KURSI SUDUT PADA UKM PENGRAJIN BAMBU DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) (Study Kasus :UD.Tiga Putri di Gunung Sari, NUSA TENGGARA BARAT) - Suartika, I Made; Triadi, A.A. ALit; Aprentari Rayes, Fira Dwika (Dinamika Teknik Mesin, 2014)
The more demands of the consumers for quality product have made the industry develop product which can satisfy the customers. This study aimed at finding out the design process and the product development which observed the customer’s needs and wants, and developed the initial design to obtain the design which met customer’s wants and needs.This study employed QFD method to identify the Voice of Customers (VoC). VoC was obtained through questionnaire, distibuted to 90 customers from 3 UKMs, i.e. UD Tiga Puteri, and two competitor UKMs, UKM Debu and UKM Mia Bamboo Collection. The questionnare distribution was undertaken to find the lavel of the customer’s interest, so that the UKM needed to develop a new product which met the customers’ satisfaction.From the three studied design, the old design (A) and the two new designs (B and C), the new desigm of chair (C) was the most appealing to the customers, with the average grade of 4.26, and the least appealing was the chair with the design (A) with the average score of 3.54. As for the bamboo chair product development according to the priority for improvement were, respectively, finishing process with priority contribution of 5.7, the strength value with the priority contribution of 2.5, durability with priority contribution of 1.9, and the aspect with the lowest priority value was colour with the score of 0.9.